2007
DOI: 10.1124/jpet.106.117952
|View full text |Cite
|
Sign up to set email alerts
|

Building Individualized Medicine: Prevention of Adverse Reactions to Warfarin Therapy

Abstract: Warfarin is the most widely used oral anticoagulant in the world for patients with venous thrombosis, pulmonary embolism, chronic atrial fibrillation, and prosthetic heart valves. Approximately 30 genes contribute to therapeutic effects of warfarin, and genetic polymorphisms in these genes may modulate its anticoagulant activity. In contrast to monogenic pharmacogenetic traits, warfarin drug response is a polygenic trait, and development of diagnostic tools predictive of adverse reactions to warfarin requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 53 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…For the present study, we attempted to validate reported associations between warfarin dose and candidate genetic variants. For this study, candidate genes were selected based on published reports [10,14] and also on biological plausibility relating to warfarin and vitamin K function and metabolism. For example, vitamin K 1 is absorbed from the small intestine through an apolipoprotein E (apoE) receptor specific uptake [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present study, we attempted to validate reported associations between warfarin dose and candidate genetic variants. For this study, candidate genes were selected based on published reports [10,14] and also on biological plausibility relating to warfarin and vitamin K function and metabolism. For example, vitamin K 1 is absorbed from the small intestine through an apolipoprotein E (apoE) receptor specific uptake [15].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible approach is to attempt to improve dose prediction by adding additional genetic loci to the dosing algorithm. Approximately 30 genes may impact the therapeutic effects of warfarin, and many of these have been studied to determine if sequence variations modulate the anticoagulant activity of warfarin [10]. For the present study, we tested the widely recognized CYP2C9 and VKORC1 SNPs and selected variants in five of the most promising additional candidate genes: EPHX1, APOE, PROC, CALU [11] and an additional cytochrome gene CYP4F [12].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating a patient's genetic background prior to beginning pharmacotherapy is increasingly becoming a reality in pharmacy practice. 10 Clinically important and well-characterized genetic polymorphisms have been identified as important predictors of adverse events; existing technology has made the detection and interpretation of these polymorphisms fast and easy enough to be routinely used in diagnostic centers. In the past several years, the US Food and Drug Administration has recommended genetic tests for several polymorphic enzymes including cytochrome P450 isoforms 2D6 and 2C9; thiopurine S-methyltransferase (TPMT); and vitamin K epoxide reductase complex, subunit 1.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-individual response to the drug varies due to presence of genetic sequence variant that may require several dose changes throughout the course of therapy to obtain steady INR levels [5]. Patient counselling and education will improve response to INR; therefore, achieving desired outcomes.…”
Section: Introductionmentioning
confidence: 99%